The lived experience of people who require prostheses or orthoses in the Kingdom of Cambodia: A qualitative study. Issue 3 (July 2021) - Ramstrand, Nerrolyn; Maddock, Alan; Johansson, Malin; Felixon, Lisa
Abstract: Background: There is an assumption that provision of assistive technologies, such as prostheses and orthoses, will improve the life situation of people with disabilities; however, this issue has been poorly addressed in low- and middle-income country settings. Objective: The objective of this qualitative study was to explore the life experience of people who use lower-limb prosthetic or orthotic devices in Cambodia, with a view to identifying areas in which developments can be made to improve the life experiences for prosthesis and orthosis users. Methods: Participants were recruited from 1/urban and 2/rural prosthetic and orthotic clinics, run by the same non-governmental organisation. Individual interviews were conducted in 2019 with 15 users of prosthetic or orthotic devices. Interviews were transcribed and analysed using a thematic analysis approach. Results: Three themes were identified: 1) A more positive outlook with an assistive device; 2) assistive devices reduce barriers but do not eliminate them and 3) disability creates social exclusion while assistive devices facilitate inclusion. For participants in this study, life without a prosthesis or orthosis was characterised by financial insecurity and a sense of hopelessness. After receiving an assistive device, participants experienced a greater sense of self-worth and empowerment as well as improved functional performance and social interactions. Conclusions: Disability was found to affect multiple facets of participants' lives including physical and psychosocial factors. Prosthetic and orthotic devices were experienced as being enablers of social inclusion and generally improved the life situation for individuals with disabilities in The Kingdom of Cambodia. Attention should be directed towards improving knowledge of, and access to prosthetic and orthotic services, securing a stable income for users and addressing device related problems.